2014
DOI: 10.3109/08880018.2014.906005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Patients with Thalassemia Major for Long-Term Endocrinological Complications After Bone Marrow Transplantation

Abstract: The aim of this study was to evaluate the endocrinological complications of the patients with thalassemia major (TM) who underwent bone marrow transplantation (BMT) and followed-up more than two years in our center, prospectively. "BMT group" consisted of 41 patients with TM. The mean age was 12.4 ± 5.4 years and transplantation age was mean 7.5 ± 4.9 years. Post-BMT follow-up lasted from 24 to 122 months (mean 65.07 months). Also, 32 TM patients with similar age group and same history of transfusion and chela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
7
1
Order By: Relevance
“…In a previous study, gonadal function is less prevalent in the HSCT group compared to the TDT group [4]. This finding was opposite to our findings.…”
Section: Dear Editorcontrasting
confidence: 99%
See 2 more Smart Citations
“…In a previous study, gonadal function is less prevalent in the HSCT group compared to the TDT group [4]. This finding was opposite to our findings.…”
Section: Dear Editorcontrasting
confidence: 99%
“…Despite the curative intent, long-term complications like endocrinopathies can occur and cause significant morbidity. Previous studies have shown that 14.6-68% TDT post HSCT have gonadal dysfunction [1][2][3][4], 15-52% have short stature [1,3] and 7-19% have hypothyroidism [1,[3][4][5]. Most previous studies describe the endocrinopathies but only two have compared with TDT [2,4].…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we could not find any difference in hypogonadism between transplanted patients with cGVHD compared with those without cGVHD. In the study conducted by Aldemir et al, they pointed out that HSCT age was a major important factor for preventing hypogonadism and early transplantation could decrease the risk of gonadal failure [23]. In a multicenter European study, comparing the age groups they reported that suspected infertility was less frequent in males who received HSCT treatment at the age of 13 or later than in those in whom treatment started at the ages of 1-12 [44].…”
Section: Discussionmentioning
confidence: 99%
“…The fertility characteristics of thalassemic patients undergone HSCT based on their age at the time of transplantation (< 13 years or ≥ 13 years) was analysed. This age classification was performed according to data available in our literature review [22,23]. In the post-HSCT group, patients' age at the time of transplantation did not significantly impact their hormonal status and sperm parameters.…”
Section: Subgroup Analysismentioning
confidence: 99%